A new Argyrodiaptomus (Copepoda: Calanoida: Diaptomidae) from the southwestern Brazilian Amazon - Previattelli, Daniel; Santos-Silva, Edinaldo Nelson Dos (Zootaxa, 2007)
Argyrodiaptomus paggii n. sp. is described from specimens collected in the Igarapé Boa Esperança, in the vicinity of the Samuel Reservoir, State of Rondônia, Brazil. The new species differs from its congeners by the following autapomorphies: (1) Schmeil's organ large at apex, constricted at medial portion; (2) row of setules on the outer margin of basis first leg; (3) a peculiar disposition and structure of the spinules on the inner border of the basis of male's left and right fifth leg; and (4) female's second urosomite partially fused and telescoped into the genital somite. We provide a discussion about some aspects of the morphology and geographical distribution of all members of the genus.